Public Relations in the Age of Artificial Intelligence Public Relations Meets Artificial Intelligence: Opportunities, Challenges, and the Future - Baniyassen, Sameer (Journal of Ecohumanism, 2024)
This paper examines the profound impact of Artificial Intelligence (AI) on public relations (PR) in the modern age. It explores the vast potential of AI to revolutionize the PR industry, enhancing the way professionals approach communication and media strategy. However, the paper also addresses the significant challenges that come with the implementation of AI in PR, including the need for better integration of technology with traditional PR practices. The methodology applied in this research includes an in-depth literature review of existing studies on the topic, complemented by interviews with PR professionals who offer firsthand insights into the real-world applications of AI. The results suggest that while AI holds immense potential to improve PR practices, it also introduces new challenges, such as the heightened need for data security and privacy. Furthermore, there is a risk that AI could be applied unethically. The paper concludes by recommending that PR professionals apply AI responsibly, leveraging its advantages while remaining mindful of the risks.